Manajemen Promosi Pesantren Berbasis Santri - Sunardi, Sunardi (At Tadbir: Islamic Education Management Journal, 2025)
This study aims to explore the promotional management strategies of Islamic boarding schools (pesantren) based on active student (santri) involvement at Pondok Pesantren Al-Urwatul Wutsqo Jombang. In the face of globalization and increasing competition among Islamic educational institutions, pesantren are expected to maintain their relevance not only through curriculum excellence and graduate character but also through strategic public image development. Using a qualitative descriptive approach, data were collected through direct observation, in-depth interviews with pesantren administrators, active students, and alumni representatives. The findings reveal that the pesantren's promotional efforts are implemented through four main approaches: empowering social media, deploying students for community-based preaching (dakwah), mobilizing alumni networks (particularly ISMA’U NTB), and organizing both internal and external events that are communicative and participatory. Students are positioned not only as learners but also as promotional agents who construct positive narratives about the institution. This study indicates a paradigm shift in religious institutional promotion-from conventional approaches to more contextual, participatory strategies. It offers practical contributions for pesantren to develop sustainable, student-driven promotional systems and aligns with the mandate of Law No. 18 of 2019 on Pesantren, which emphasizes pesantren’s independence and strategic role in society.